Problems and solutions for the diagnosis of gestational diabetes mellitus in non metropolitan areas in India - Seshiah, V.; Bhavatharini, N.; V. K., Sanjeev; A. R. A., Changanidi; Aruyerchelvan, R. (International Journal Of Community Medicine And Public Health, 2020)
Management of gestational diabetes mellitus and hyperglycemia in pregnancy is challenging in developing country like India. There are several logistic, socioeconomic and cultural issues faced by the care providers and the patients alike. In order to tackle these challenges, Diabetes in Pregnancy Study Group of India (DIPSI) recommendations consisting of a single glucose challenge test is ideal to evaluate the glucose intolerance and early initiation of doctors’ prescription. This review article explores the practical challenges associated with managing gestational diabetes mellitus and recommendations to overcome these challenges in the public health system.